Effectiveness of using methods for extraction of chemical elements into solution when sample preparation of soil samples - Pazniak, Sergei S.; Stepanyuk, Mikhail (Journal of the Belarusian State University. Ecology, 2024)
In our studies, we studied the effectiveness of using (applicability) of various methods for extracting heavy metals (chemical elements) into solution during sample preparation of soil samples for routine determination of heavy metals using inductively coupled plasma atomic emission spectroscopy. According to the information available in the scientific literature, the effectiveness of acid decomposition methods in terms of the degree of impact on the soil increases in the following order: decomposition by boiling in an open container → decomposition in an autoclave → decomposition in a microwave oven. This is due to the fact that when a sample is decomposed by boiling with a mixture of acids in an open system, a loss of elements occurs due to volatilization, as well as due to their secondary absorption by the insoluble soil residue containing a large amount of iron hydroxides reactive towards heavy metals. The use of different options for microwave acid decomposition of soils should be carried out depending on the set of elements being studied. Incomplete acid decomposition is carried out in the case of analyzing a limited set of heavy metals, which makes it possible to simplify the decomposition procedure, reduce the overall analysis time, and eliminate the use of harmful chemical reagents without compromising the quality of the results obtained. Isolation of elements associated with soil organic matter for some types of extraction was carried out by adding 30 % H2O2 and allowing the sample to sit for 10 minutes before diluting the sample, but after microwave digestion. During the research, it was found that the most effective way to extract heavy metals (chemical elements) from soil into solution is extraction using the decomposition method with aqua regia. The method of decomposition of soil (chemical elements) with nitric acid can be used in the absence of other sample preparation alternatives and also gave acceptable decomposition results for assessing soil contamination with heavy metals. Extraction of samples in nitric acid with the addition of 30 % hydrogen peroxide significantly increases the oxidizing ability of nitric acid and eliminates contamination of samples with foreign substances.